Pengaruh Media Sosial Terhadap Kesehatan Mental Remaja - Agus Iryadi; Chika Afiana Adriani; Naira Salwa Qabila Pertiwi; Ririn Rahmawati; Zahgrina Dewi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Currently technology, especially social media, cannot be separated from society, many people around us, especially teenagers, are very dependent on social media. According to a 2015 study, over 2,000 teenagers accessed social media on their phones 92% of the time. Social media has many positive influences that we can accept but there are also many negative influences that occur due to social media, especially in mental health, mental health is very important in the current era because there are many teenagers who experience depression due to playing social media,Many teenagers also try to end their own lives because of the ridicule they get when playing on social media. Teenagers should be able to live their lives well without having to think about the negative impacts they receive as a result of playing on social media, for example cyber bullying. As a result, all stakeholders need to focus more on mental health due to social media, especially in teenagers.